Kinetics of Ion Exchange in Duolite A-161 - Lokhande, R.S.; R.D.Tiwari, Santoshi (Asian Journal of Chemistry, 2010)
The rate of exchange between radioactive bromide ions on a resin and bromide ions in a solution has been studied. The investigation was carried out by varying the amount of bromide ion concentration of electrolyte (KBr) in the range of 0.005 M to 0.1 M and at various temperatures ranging from 27 to 50ºC. Subsequently, the energy of activation was also calculated.